Edukasi dan Sosialisasi Perilaku Hidup Bersih dan Sehat (PHBS) Pada Masyarakat Desa Betung Selatan - Yeti Atriyani; Rensalia Pramita; Shabilla Putri W; Esta Miranda; Anggy Lorenza; Larasari Putri; Rara Suci S; Rifka Dela Gebyka; Junianto Junianto; Aprian Aprian; Lilis Sukma Dewi; Malita Malita; Marita Eka Sari; Rizki Agustri Wahyudi (JURNAL PENGABDIAN KADER BANGSA, 2026)
Clean and Healthy Living Behavior (PHBS) is a habit applied by the community in daily life to achieve optimal health. The PHBS education and socialization program in Betung Selatan Village aims to increase public awareness of the importance of healthy living behavior. The methods used include counseling, demonstrations, and community satisfaction surveys. The results showed an increase in awareness of maintaining environmental cleanliness and implementing a healthy lifestyle. Survey results show that 85% of residents routinely wash their hands with soap, 90% have closed trash bins, and 80% adopt a healthy diet. This study emphasizes the importance of health education as part of efforts to improve the quality of life of the community.